A rare case of posterior spinal cord syndrome following commando surgery: A case report and review of literature - Bharat R Dave; Saral J Patel; Ravi B Patel; Akruti M Dave (Indian Spine Journal, 2023)
A 60-year-old male who underwent commando surgery for oral cancer in a supine position and 20-degree neck extension developed sensory ataxia with a loss of proprioception in bilateral lower limbs and hands in the immediate postoperative period. The magnetic resonance imaging (MRI) of brain and screening of spine done within 6 h of surgery indicated a degenerative cervical canal stenosis from C3 to C7 level. A final diagnosis of posterior spinal cord syndrome (PCS) was made after excluding other causes clinically and radiologically. Emergency surgical decompression in the form of C3–C7 laminectomy and intravenous methylprednisolone were administered within 12 h of index surgery. An early diagnosis and treatment resulted in a good neurological recovery by the seventh postoperative day and he was ambulatory with minimal support at 3-month follow-up.